(untitled) - Greata, Joanne; Joanne Greata (Clifton Park, NY, 2006)
Establising music in early childhood education: a historical perpective, Current research regarding music and music nurturing, What types of activities musically nuture young children?
Keywords: Music; Early childhood education; Preschool music